Hd1, Ghd7, and DTH8 synergistically determine the rice heading date and yield-related agronomic traits. (May 2022) - Sun, Kangli; Huang, Minghui; Zong, Wubei; Xiao, Dongdong; Lei, Chen; Luo, Yanqiu; Song, Yingang; Li, Shengting; Hao, Yu; Luo, Wanni; Xu, Bingqun; Guo, Xiaotong; et al.
Abstract: Heading date determines the seasonal and regional adaptation of rice ( Oryza sativa L.) varieties and is mainly controlled by photoperiod sensitivity (PS). The core heading date genes Hd1, Ghd7, DTH8, and PRR37 act synergistically in regulating the PS. In this study, we systematically analyze the heading date, PS, and agronomic traits of eight homozygous lines with various combinations of Hd1, Ghd7, and DTH8 alleles in the prr37 background under long-day (LD) and short-day (SD) conditions, respectively. We find that Hd1 alone promotes heading, regardless of the day length. However, under LDs, Hd1 suppresses flowering, in coordination with functional Ghd7 or with Ghd7 and DTH8 . These loci cooperate to negatively regulate the Ehd1 - Hd3a / RFT1 pathway and delay heading. Under SDs, Hd1 competes with various heading suppressors to promote heading. Therefore, the dual function of Hd1 is vital for PS. The lines carrying Hd1 alone show reduced plant height with fewer primary and secondary branches in panicles. Lines carrying Ghd7 and DTH8 (with hd1 ) show delayed heading and improve agronomic traits. Overall, our results reveal the regulation of rice PS flowering by the core heading date genes and their effects on agronomic traits, providing valuable information for the selection of rice varieties for adaptation to different light and temperature conditions.